United State - Iran Relations 1941-2020 - Tarawneh, Sahar Mohammad (Opción, 1970)
U.S-Iran relations rooted back to the second half of the 1950s decade of the twentieth century. The relation witnessed close cooperation with Shah of Iran and was very solid during the decades follow. USA provides Iran with all needed assistance either economic, military. By the 1979 Islamic relations the relations turned out 180 degrees. The relations witnessed some cooperation between the two countries and for a very short time according to the two countries interests. Iran Nuclear program plays a main role of increasing the tension between the two countries. Obama's administration exerts its best efforts to finalize Iran’s nuclear program and it succeeded in singing the deal between (5+1) countries in 215. Trump administration changed the whole situation through withdrawal from the agreement and the relations escalated again.